A novel quinolinyl-tetraphenylethene-based fluorescence "turn-on" sensor for Zn2+ with a large Stokes shift and its applications for portable test strips and biological imaging. (2nd October 2020) - Xu, Jianxing; Xiong, Jingwen; Qin, Yanlin; Li, Zongzhi; Pan, Chengqiang; Huo, Yanping; Zhang, Haoli
Abstract : A new 8-hydroxyquinoline derivative TPE(OH)-8HQ, has been synthesized and evaluated as an efficient fluorescence "turn-on" sensor for detection of Zn 2+ based on the chelation-enhanced fluorescence (CHEF) mechanism in neutral aqueous solution. Abstract : A new 8-hydroxyquinoline derivative bearing the hydroxytetraphenylethene moiety, TPE(OH)-8HQ, has been designed, synthesized and evaluated as an efficient fluorescence "turn-on" sensor for detection of Zn 2+ based on the chelation-enhanced fluorescence (CHEF) mechanism in neutral aqueous solution. The free sensor displays a weak fluorescence emission at 470 nm; upon addition of Zn 2+, its emission peak red-shifted from 470 nm to 607 nm and the emission intensity at 607 nm was increased 17-fold, showing fluorescence "turn-on" recognition for Zn 2+ without interference from same group elements such as Cd 2+ /Hg 2+ . Moreover, TPE(OH)-8HQ achieved a low detection limit of 1.64 × 10 −7 M and exhibited a large Stokes shift (289 nm) after the addition of zinc ions, effectively eliminating background interference for live cell imaging. Through the control experiments using two analogues without a hydroxyl in the TPE, TPE-8HQ and TPE(OCH3 )-8HQ, we find that as these two analogous cannot distinguish Zn 2+ from Cd 2+, the bonding interactions of the hydroxyl group of TPE with Zn 2+ are crucial for selective detection of Zn 2+ ions. Additionally, the mechanism of the interaction process between TPE(OH)-8HQ and Zn 2+ was studied in detail by UV/fluorescence titration and NMR analysis. The Job plot and mass spectrometry analysis indicated that TPE(OH)-8HQ forms a 2 : 1 complex with Zn 2+ . Most importantly, TPE(OH)-8HQ was successfully used for imaging Zn 2+ in living cells and in the fabrication of simple test strips for on-site and rapid sensing of Zn 2+ ions in aqueous solution.